BINODINI DEVI'S ‘AMAR KATHA’: AN ACTRESS LIFE THROUGH HER AUTOBIOGRAPHY - Bhattacharjee, Arundhuti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Binodini Debi became one of the first professional actresses when she began working in theaters in 1874, she was part of the first generation of female recruits who were paid to work in theaters. Binodini Debi was brought to the world in 1863 in Kolkata. She was the main acclaimed entertainer of Bengali theatre and one of the incomparable greats who walked the path of Bengali theatre. She was introduced to the bleeding world in cash light locales in Kolkata and was a prostitute until Girish Chandra Ghosh took her to mainstream Bengali theatre. Binodini is by no means a feminist. She brings a feminist perspective to her portrayal of women and their experiences and to her works. It describes Binodini's writing process and about the exploitations of Bengali theatre.